Analisa Lama Penggunaan Kumbung terhadap Produktivitas Jamur Merang (Volvariella volvaceae) - Hulyadi, Hulyadi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Lingkungan, kualitas media, teknik inokulasi bibit dan kualitas bibit menjadi beberapa faktor yang mempengaruhi produktivitas jamur merang. Kondisi lingkungan menjadi salah satu faktor utama. Kondisi lingkungan ideal harus terus dijaga petani jamur merang, produksi jamur merang tetap setabil. Suhu ruangan menjadi faktor yang harus diperhatikan untuk menjaga tumbuh kembang jamur merang. Suhu ruangan bisa ideal jika kondisi kumbung dan kualitas media terjaga. Peneliti ini bertujuan menganilsa produktivitas kumbung selama satu tahun pertama produksi. Produktivitas diukur melalui lama produksi dan massa jamur merang yang diperoleh. Produksi jamur merang rata-rata dalam setiap bulannya sebesar 103,7 Kg dengan lama produksi rata-rata 30 hari. Korelasi anatara jumlah produksi dan lama panen berkorelasi positif ini dibuktikan dengan nilai R hitung 0,978>R tabel 0, 4575. Berdasarkan kajian lapangan dan analisis data diperoleh jumlah produksi berkorelasi positif dengan lama panen dan produksi jamur dan akan menurun seiring bertambahnya usia kumbung. Menurunnya produktivitas diakibatnya karena menurunnya kualitas media tanam. Kontaminan dan sulitnya merekayasa iklim kumbung menjadi faktor lain yang berpengaruh terhadap menurunnya jumlah dan lama produksi jamur merang. Analysis of the Length of Use of Kumbung on the Productivity of Straw Mushrooms (Volvariella volvaceae) Abstract The environment, the quality of the media, the inoculation technique of seedlings and the quality of seedlings are some of the factors that affect the productivity of the straw mushrooms. Environmental conditions are one of the main factors. Ideal environmental conditions must be maintained by straw mushroom farmers, the production of straw mushrooms remains as stable as possible. Room temperature is a factor that must be considered to maintain the growth and development of straw mushrooms. Room temperature can be ideal if the condition of the kumbung and the quality of the media are maintained. This researcher aims to analyze the productivity of the kumbung during the first year of production. Productivity is measured through the length of production and the mass of the acquired straw mushroom. The average production of straw mushrooms in each month is 103.7 Kg with an average production duration of 30 days. The correlation between the amount of production and the duration of harvest is positively correlated with the calculated R value of 0.978>R table 0.4575. Based on field studies and data analysis, the amount of production is positively correlated with the length of harvest and mushroom production and will decrease with age. The decline in productivity is due to the decline in the quality of the growing media. Contaminants and the difficulty of engineering a continuous climate are other factors that influence the decrease in the number and duration of straw mushroom production.